SOCIAL MOVEMENTS, DEMOCRACY, AND POLITICAL COMMUNICATION IN LATIN AMERICA - Martin-Vicente, Maximiliano [UNESP]; Kraus-Luvizotto, Caroline (Taylor & Francis, 2024)
The implications of political communication for democracy focus on the need to promote greater citizen participation in political processes and ensure the plurality and diversity of voices in the public sphere. Observing political communication today, the action of social movements draws attention. This chapter presents a historical approach to social movements in Latin America and their relationship with democracy, from the 1980s to the present, raising considerations about movements, social counter-movements, and political communication. Political communication is a field of mediation between movements and counter-movements, which provides elements for the former to achieve the necessary visibility and disseminate their causes. The communication dynamics of social movements, as opposed to the narratives of counter-movements, is an important mechanism to defend their political agendas and promote broader social changes.